Efeitos do ácido p-metoxicinâmico sobre o crescimento e metabolismo antioxidante de soja (Glycine max) - Silva, Karla Gabriela da (2017)
In community life, plants compete for water, nutrients, light, among others. This interferes with species survival in an ecosystem. The perception by neighboring plants is given by the release of compounds in the soil. They are called allelochemicals, and are formed from plant secondary metabolism. These compounds can inhibit or activate physiological processes in plants. In this context, the effects of different concentrations of allelochemical p-methoxycinnamic acid (AMC) on the growth and antioxidant metabolism of soybean roots were evaluated. In general, the data showed that the stress caused by the allelochemical resulted in: 1) reductions of the lengths of the roots and stems, with subsequent decrease in fresh biomass, but few influence on dry biomass; 2) reductions in leaf area and fresh and dry biomasses; leaves were more affected than roots and stems; 3) relevant foliar necrosis after joint application of AMC with Aureo® or acetone; 4) increased activities of antioxidant enzymes (POD and CAT) and production of reactive oxygen species (EROS), and reduction of lipid peroxidation. Taken together, these results indicate that AMC affected roots, stems and leaves of soybean, followed by an antioxidant response involving related enzymes to combat the oxidative stress.